Physical geography and closed loop recycling - Fullen, Michael A. (Hungarian Geographical Bulletin, 2015)
There is a growing body of research projects spanning over three decades that have provided insights into the concept of waste management, a topic standing in the focal point of environmental issues. In this paper, the 'SHASEA Project,' 'BORASSUS Project,' Yuanyang Project' and 'Cradle to Cradle BIZZ Project' are summarized and integrated to present a revised philosophical view that nature has no concept of 'waste.'The 'Sustainable Highland Agricultural in South East Asia' (SHASEA) Project funded by the European Union was established to promote sustainable agro-environmental development in the highlands of South-East Asia. The Project examined the effectiveness of selected agronomic and soil conservation treatments by using both modified and novel cropping practises within farmer-managed small fields. The EU-funded BORASSUS Project was aimed to evaluate the long-term effectiveness of biological geotextiles in controlling soil erosion and assessing their sustainability and economic viability. Biological geotextiles offer potentially novel bioengineering solutions to environmental problems (e.g., soil conservation, sustainable plant production and improved ecosystem management). Biogeotextiles may provide socio-economic platforms for sustainable development and the benefits for developing countries. A complex and sustainable agro-environmental system of terraced rice paddy fields in Yuanyang developed by Hani minority people of Yunnan Province was the basis of the most illuminating projects which teaches us many lessons on waste management, the 'Agro-environmental sustainability of the Yuanyang rice terraces of Yunnan Province, China'. The Hani people have maintained this intricate and elaborate system for over 1,300 years. If we can understand how this system is sustained, we can learn lessons which hopefully can be applied more generally. The innovative approach of 'Cradle to Cradle' (C2C) technology promotes and develops closed loop recycling. At the end of a useful life time, C2C items are disassembled and reassembled for other uses. Lessons from the 'C2C BIZZ' Project (funded by the EU 'INTERREG IVB North West Europe Programme) are also reviewed in this study.